2021
DOI: 10.1186/s42358-021-00186-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk comorbidities in rheumatoid arthritis patients and the use of anti-rheumatic drugs: a cross-sectional real-life study

Abstract: Background Rheumatoid arthritis (RA) is a common autoimmune systemic inflammatory disease. In addition to joint involvement, RA patients frequently have other comorbidities, such as cardiovascular diseases. Drugs used for RA treatment may increase or decrease the risk of a cardiovascular event. This study aims to analyze cardiovascular risk comorbidities in patients with RA and the correlation with the use of anti-rheumatic drugs. Methods Cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Controlling the inflammatory process with DMARDs, especially targeted therapy, is linked to a lower risk of CVD [ 145 , 146 ]. A recent cross-sectional real-life study reported that the use of less glucocorticoids and an increasing use of bDMARDs in patients with cardiovascular comorbidities suggested that rheumatologists have become aware of the potential influence that RA drugs may have on comorbidities [ 147 ].…”
Section: Clinical Aspects Of Ramentioning
confidence: 99%
“…Controlling the inflammatory process with DMARDs, especially targeted therapy, is linked to a lower risk of CVD [ 145 , 146 ]. A recent cross-sectional real-life study reported that the use of less glucocorticoids and an increasing use of bDMARDs in patients with cardiovascular comorbidities suggested that rheumatologists have become aware of the potential influence that RA drugs may have on comorbidities [ 147 ].…”
Section: Clinical Aspects Of Ramentioning
confidence: 99%
“…Various studies carried out before the pandemic documented a prevalence of 15% in patients with RMD, which was reflected in studies carried out during the pandemic, where the prevalence of diabetes mellitus in patients with RA was 14.9% [ 19 , 51 ], although in another study carried out in 2021, a prevalence of 25.02% was found in patients with rheumatological diseases, mainly RA and SLE [ 52 ]. These data could point to a slight increase in this comorbidity in patients with RA and SLE, although more studies are needed to clarify this potential increase.…”
Section: Comorbidities During the Covid-19 Pandemicmentioning
confidence: 99%
“…From RA patients, 280 were at risk of anxiety and 227 of depression; from SLE patients, 56 were at risk of anxiety, and 50 were at risk of depression. [ 17 ] Ireland RMDs and COVID-19 from database C19-GRA 212 625.5% ever smoked 71.7% were hospitalized ( p =0.01), and 20.4% died ( p =0.02) [ 18 ] Brazilian teaching hospitals (Ceará, Minas Gerais, and Rio Grande do Sul) Patients over 18 years of both sexes diagnosed with RA 791 15% had DM II, 9.2% had SAH, 34.3% had dyslipidemia, and 26.9% had obesity by BMI RA patients with increased WC have more CVR factors (such as DM II (31.2%), SAH (80.2%), and dyslipidemia (50.0%)) and these variables have an independent influence on the prevalence of obesity [ 19 ] Latin America, 2021 Rheumatologic patients during lockdown 3502 (1694 with RA and 1012 with SLE) Hypertension, depression, and anxiety The most common self-reported comorbidities were hypertension (669 patients; 19.1%) and depression/anxiety (455; 13.3%) [ 20 ] France (including French overseas territories) SLE patients recruited by their specialist or from AFL + 536 questionnaires from individual SLE patients Not mentioned Screening for anxiety and depression was positive for 47.6% and 41.5%, respectively. Difficulties accessing medical care were the only significantly associated factor to anxiety (OR = 1.94, p = 0.012).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the high risk of CVD in RA patients is related to the underestimation of non-traditional risk factors for CVD, as well as to suboptimal management of the disease [6]. As the degree of CVD involvement in RA correlates with the degree of systemic inflammation, basic synthetic diseasemodifying antirheumatic drugs (DMARDs) and biologic DMARDs protect against cardiovascular events, whereas chronic use of nonsteroidal anti-inflammatory drugs (NSAIDs) and glucocorticosteroids (GCs) increases CVD risk [7]. In addition, in patients with active RA, in contrast to the general population, an increased rate of cardiovascular events and mortality is paradoxically associated with a decrease in the level of circulating lipids [8,9].…”
Section: Introductionmentioning
confidence: 99%